Geriatric falls: an enormous economic burden compared to firearms - Kartik Prabhakaran; Bardiya Zangbar; Aryan Rafieezadeh; Ilya Shnaydman; Jordan Michael Kirsch; Gabriel Rodriguez; Anna Jose; Matthew Bronstein (Trauma Surgery & Acute Care Open)
Background This study aimed to assess the medical costs, and the combined costs of fatal firearm injury and fatal falls during a 5 year period. While fatal firearm injury represents a significant public health concern, the healthcare community is faced with the significant challenge of fatal falls, particularly in light of the elderly population growth.Methods Data were exported from the Web-based Injury Statistics Query and Reporting System database for fatal firearm and falls in patients aged between 15–85 years-old. The primary outcome was medical cost and the secondary outcome was combined costs (combination of medical costs and value of statistical life).Results The medical cost of fatal falls was significantly higher in 2015–2020 in all age groups. The combined cost was significantly higher in fatal firearm injury overall. We found the combined cost was higher in fatal falls after 2019 for patients in the 45–85+ age range. During 2015–2019, the percentage of fatal falls had a significant increase in all age ranges, with a rise in the slope in 2019 for patients over 65 years. The annual percent change (APC) for the proportion of fatal falls increased from 2015 to 2020, there was a significant increase in the slope after 2019 (2.81% APC before 2019 vs 6.95% after 2019).Conclusion Geriatric fatal falls have significantly higher medical costs compared with fatal firearm injury. The combined cost for fatal falls exceeded fatal firearm injury after 2019 which highlights the increasing socioeconomic burden of an aging population.Level of evidence Level III retrospective study.